Problem matematyczności przyrody - Mrozek, Jarosław (Filozofia Nauki, 2004)
The aim of this paper is a presentation, specification and criticism of the thesis proclaiming the mathematicality of nature. The author distinguishes between the structural and the functional aspects of this thesis. With such an interpretation this thesis has a strong methaphysical interpretation. However such thesis is linked with some problems, concerning the issue of its verification. Therefore the author proposes to consider a neutral thesis proclaiming that nature is amathematical. Then we avoid strong assumptions concerning the structure of the world and better understand not only the successes but also failures of mathematical methods. Besides we gain a new view of the issue of efficacy of mathematical methods in natural sciences.